Hindī-gadya kā vikāsa, arthāt, Hindī-gadya kā ādi se āja taka kā vivecanātmaka itihāsa - Jijñāsu, Mohanalāla, 1922- (SAMP early 20th-century Indian books project, 1949)
History of Hindi prose literature.